Fatigue Crack Growth in A 7075 Al-Alloy with Evaluation of Overloading Effects - Ivo Cerny (Communications - Scientific letters of the University of Zilina, 2012)
Measurement of fatigue crack growth (FCG) in an Al 7075-T7351 alloy of a particularly high homogeneity was carried out as a part of the Proficiency Test Programme on fatigue crack growth measurement, organised by General Electric Aviation, USA, in collaboration with the company Exova in France. To pass the test programme successfully, a particular attention was paid to improve and verify DCPD (direct current potential drop) method being used for the crack length measurement. Additionally, an investigation of effects of overloads on fatigue crack growth and retardation was carried out. In the CT specimens used, the difference between actual and calculated crack length at the crack starting point was quite significant, approximately 4.3 mm. However, the difference as a function of crack length was almost constant. Results of FCG rates were very self consistent, likely due to the material homogeneity. Values of the parameters C and m measured at the SVÚM a.s. laboratory were evaluated as the third best precise from all the 16 worldwide participating laboratories. Retardation effects of overloads of the magnitudes 2.7-times and 3.0-times of the maximum load in the constant range fatigue loading were significant. The overloads resulted in substantial crack closure effects, which, however, did not occur immediately, but just after further fatigue crack extension, comparable with plastic zone size.